A quick history of money : from bartering to Bitcoin - Gifford, Clive; Flowers, Rob (Gifford, Clive. Quick histories., 2021)
"Why is a $5 bill worth $5? Where do coins come from? What do banks actually do? Discover the answers to these and more in this crash course from ancient cashless societies to ... very modern cashless societies. The history of buying, selling, saving, and stealing is full of crazy stories and unbelievable facts, proving that while it might sound all grown-up and series, money sure is funny." -- Back cover.